PERANCANGAN SISTEM INFORMASI PERPARKIRAN BERBASIS WEB PADA PUSAT PERBELANJAAN ANEKA SUBUR KOTA TANGERANG - Halili Maar; Farizi Ilham; Dimas Lendensi (Journal of Research and Publication Innovation, 2025)
In the midst of the current technological developments, especially in information technology who developed such a tool that can be used to alleviate human activities so as to become more efficient, accurate and optimal, in an enterprise accuracy and optimal in doing something that is needed, so the company developed faster, because the purpose of business is to make a profit by exploiting all available resources. At this time a lot of resources that can be used for business one that is growing is a parking area at each place of business definitely provides a parking area. In the Shopping Center Arts Aneka Subur Tangerang City parking only managed using a system of parking tickets, and therefore there are still many problems that arise, for example, the safety factor is very less, the length of the data recording parking and vehicle parking fee uncertain and earnings parking which is typically not it can be seen every day. With these problems, the author tries to provide alternative solutions to problems with building information systems for data processing parking of vehicles using the programming language PHP and MySQL database, as well as the editor Adobe Dreamweaver CS5. The author hopes that this information system can help park the Arts Shopping Center Aneka Subur Tangerang city, so that they can serve their customers better again.